Taking care of people experiencing homelessness: a community case study on the practice of the Volunteer Association “A doctor for you” in Brescia, Italy - Pasini, A.; Pasini, E.; Puccio, F.; Seddio, C.; Bocci, P.; Lovati, R.; Amadini, M. (Frontiers in Public Health, 2025)
IntroductionAlthough homelessness is a much-studied phenomenon today, statistics indicate a steady increase in homelessness globally. UN General Assembly itself recommends implementing strategies through the commitment of the various stakeholders involved, among which health services are at the forefront. This current community case study details a specific research-practice partnership strategy—led in Brescia (Italy) in 2023 by the Association of volunteer doctors “Un Medico x Te” (A doctor for you) and the Research Center on Family and Childhood Education (CESPEFI) of the Università Cattolica del Sacro Cuore—as an attempt to deepen the evaluation of peoples experiencing homelessness' health conditions in Brescia urban area and to promote best practices in granting population experiencing homelessness sustainable health-care approaches.MethodIn phase 1, since chronic liver diseases are very common in people experiencing homelessness, to investigate the presence of these pathologies, the Association “Un Medico x Te” carried out a preliminary observational retrospective echocardiographic cohort study in the population experiencing homelessness hosted in Brescia's housing services. In phase 2, CESPEFI led a research project to investigate the way health and healthcare is conceived by the homeless population living in Brescia urban area, according to the ethnographic methodological framework. Qualitative data were coded to explore emerging themes concerning the best practices to approach the population experiencing homelessness and to grant them appropriate care. At the end of the process internal guidelines were drawn up, based on greater attention to the relationship between doctors and patients experiencing homelessness and to the sustainability of the care-process.ResultsChronic hepatic diseases were more common and severe in people experiencing homelessness than general population and it was related to the duration of the homeless condition. Taking care of the particular aspects of the relationships between doctors and patients experiencing homelessness made clinical research and health care more effective.DiscussionThis study demonstrates that a multi-disciplinary approach is strategic in order to respond to such a complex phenomenon as homelessness is; not-adopting a multidisciplinary approach may itself represent an additional mechanism of exclusion. Further studies are needed to explore innovative strategies to better face the problem of how: 1) to approach patients experiencing homelessness and 2) to implement appropriate medical assistance.